2014
DOI: 10.1161/atvbaha.114.303889
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormones and Coronary Artery Calcification in Euthyroid Men and Women

Abstract: Objective— Overt and subclinical hypothyroidism are risk factors for atherosclerosis. It is unclear whether thyroid hormone levels within the normal range are also associated with atherosclerosis measured by coronary artery calcium (CAC). Approach and Results— We conducted a cross-sectional study of 41 403 apparently healthy young and middle-aged men and women with normal thyroid hormone levels. Free thyroxin, free triiodothyronine, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 35 publications
4
38
1
1
Order By: Relevance
“…In line with this concept, low-normal thyroid function is associated with a greater increased intima media thickness (cIMT), an established biomarker of subclinical atherosclerosis [3, 4]. Furthermore, low-normal thyroid function is associated with increased coronary artery calcification [5] and progression thereof [6], although an association of a high-normal TSH level with increased coronary heart disease risk has been variably reported [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…In line with this concept, low-normal thyroid function is associated with a greater increased intima media thickness (cIMT), an established biomarker of subclinical atherosclerosis [3, 4]. Furthermore, low-normal thyroid function is associated with increased coronary artery calcification [5] and progression thereof [6], although an association of a high-normal TSH level with increased coronary heart disease risk has been variably reported [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Although the CAC score is a reliable surrogate marker of atherosclerotic vascular changes when it is measured by MDCT, only a few studies have observed an association between thyroid hormone levels and CAC in euthyroid individuals. 19,20,23 One study found that FT4, but not TSH, was inversely associated with the CACS in men but not in women. Another study with a larger sample size (n = 41 403) found that both FT4 and TSH were inversely associated with the CACS.…”
Section: Discussionmentioning
confidence: 99%
“…It is not yet clear whether variations in thyroid hormone levels within the normal range are associated with subclinical atherosclerosis as measured by the CACS. However, one large cohort study found that low‐normal free thyroxin and thyroid‐stimulating hormone (TSH) levels were associated with higher prevalences of subclinical coronary artery disease, specifically, atherosclerosis as measured by the CACS . Another study of euthyroid individuals found an inverse association between free thyroxin (FT4) and coronary artery calcification (CAC) in men .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a cohort of over 41 thousand healthy young and middle-aged euthyroid men and women, low levels of normal free thyroxin and thyroid-stimulating hormone were associated with a higher prevalence of coronary calcification 55 .…”
Section: Leveraging Biomarkers To Guide Interventionmentioning
confidence: 98%